PRELIMINARY STUDY OF THE BIOLOGY AND MORPHOLOGY OF Cyrtomenus bergi Froeschner, NEW PLAGUE OF YUCCA - GARCÍA-G., CÉSAR A.; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 1980)
Beginning in 1980, in the county of Caicedonia (Valle) the new pest C. bergi (Hemiptera: Cydnidae), commonly named the "subterranean chinch bug" or "smallpox bug", was found attacking roots of the cassava variety "Chiroza Gallinaza" (Manihot esculenta Crantz) affecting the root quality. Given its incidence and its potential as a pest, the present studies were undertaken in the laboratory (average temperature 23°C and relative humidity 65%) at the Internacional Center of Tropical Agriculture, Palmira, Valle. The adult chinch bugs have an oval body, 7,1 mm long, are dark brown to black in color, with spined tibiae and the first pair of legs fitted for burrowing The duration of the egg stage is 13,6 days; the nymphs pass through five instars totaling 111,2 days and the adult, longevity is more than 250 days. The different insect stages are described.